Cardiac output and related haemodynamics during pregnancy: a series of meta-analyses. Issue 7 (21st January 2016) - Meah, Victoria L; Cockcroft, John R; Backx, Karianne; Shave, Rob; Stöhr, Eric J
Abstract : Objective: Cardiac output, a fundamental parameter of cardiovascular function, has consistently been shown to increase across healthy pregnancy; however, the time course and magnitude of adaptation remains equivocal within published literature. The aim of the present meta-analyses was to comprehensively describe the pattern of change in cardiac output during healthy pregnancy. Method: A series of meta-analyses of previously published cardiac output data during healthy, singleton pregnancies was completed. PubMed and Scopus databases were searched for studies published between 1996 and 2014. Included studies reported absolute values during a predetermined gestational age (non-pregnant, late first trimester, early and late second trimester, early and late third trimester, early and late postpartum). Cardiac output was measured through echocardiography, impedance cardiography or inert gas rebreathing. Observational data were meta-analysed at each gestational age using a random-effects model. If reported, related haemodynamic variables were evaluated. Results: In total, 39 studies were eligible for inclusion, with pooled sample sizes ranging from 259 to 748. Cardiac output increased during pregnancy reaching its peak in the early third trimester, 1.5 L/min (31%) above non-pregnant values. The observed results from this study indicated a non-linear rise to this point. In the early postpartum, cardiac output had returned to non-pregnant values. Conclusion: The present results suggest that cardiac output peaks in the early third trimester, following a non-linear pattern of adaptation; however, this must be confirmed using longitudinal studies. The findings provide new insight into the normal progression of cardiac output during pregnancy.